2007
DOI: 10.4161/cbt.6.7.4324
|View full text |Cite
|
Sign up to set email alerts
|

p14ARF sensitizes human osteosarcoma cells to cisplatin-induced apoptosis in a p53-independent manner

Abstract: The tumor suppressor p14ARF, encoded by the INK4a/ARF locus, is often disrupted in human cancers. p14ARF triggers cell cycle arrest and sensitizes cells to apoptosis in the presence of collateral signals. To investigate the role of p14ARF in chemotherapeutic drugs-induced apoptosis, p14ARF was overexpressed by stable transfection in human osteosarcoma cell lines, U2OS (p53-wt/p14ARF-null) and MG63 (p53-mt/p14ARF-null). The results showed that ectopic p14ARF sensitized both cell lines to cisplatin-induced cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The knockdown of ANRIL expression impaired cell proliferation, migration and invasion, and induced cell apoptosis in esophageal cancer, gastric cancer, and lung cancer cell lines [13,14] . ANRIL controlled the epigenetic silencing of p14ARF and p16INK4a, which were important regulators of apoptosis induced by cisplatin [15][16][17] . The results also revealed that ANRIL rs1333049 was associated with the incidence of severe gastrointestinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of ANRIL expression impaired cell proliferation, migration and invasion, and induced cell apoptosis in esophageal cancer, gastric cancer, and lung cancer cell lines [13,14] . ANRIL controlled the epigenetic silencing of p14ARF and p16INK4a, which were important regulators of apoptosis induced by cisplatin [15][16][17] . The results also revealed that ANRIL rs1333049 was associated with the incidence of severe gastrointestinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results demonstrate that MILIP links c-Myc to inactivating p53. This regulation appears independent of p14 ARF as the cell lines used (A549, MCF-7, HCT116, MDA-MB-231, and U2OS) were deficient in p14 ARF expression [37][38][39][40][41][42][43] . Fig.…”
mentioning
confidence: 99%
“…On its own, p14 ARF did not induce apoptosis, but rather sensitized cells to apoptosis in the presence of camptothecin and adriamycin, inhibitors of topoisomerase I and II, in osteosarcoma, colorectal, melanoma, and fibroblast cell lines [ 121 ]. This effect is also observed in osteosarcoma cell lines in response to cisplatin-induced apoptosis, however, effects were independent of p53 [ 122 ], suggesting a distinct regulatory mechanism that may be treatment dependent.…”
Section: Clinical Implications Of Cdkn2a: Impact On Response and Rmentioning
confidence: 87%